2016
DOI: 10.1007/s00259-016-3545-8
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of SPECT/CT for sentinel node localization in patients with ipsilateral breast cancer relapse

Abstract: BackgroundIn recent years repeat sentinel node (SN) biopsy has been proven to be feasible in local breast cancer recurrence (LBCR). However, in these patients SNs outside the ipsilateral axilla are frequently observed. This study evaluates the contribution of SPECT/CT for SN localization and surgical adjustment in LBCR patients.MethodsSN biopsy was performed in 122 LBCR patients (median age 60.5 years, range 24–87), enrolled from August 2006 to July 2015. Median disease-free time lapse was 109.5 months (range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 28 publications
1
11
0
1
Order By: Relevance
“…The radiotracer of lymphoscintigraphy can enter lymphatic capillaries via the gaps between cell junctions and the intercellular clefts formed by overlapping cells, followed by the lymphatic drainage, and finally gathered in the SLNs to form as a "hot spot" on SPECT image. The SPECT/CT was able to provide functional and anatomical information simultaneously, and locate IM-SLN more accurately (23). Based on these, in our current study, we try to find out the relationship between IM-SLN and consensus guidelines.…”
Section: Discussionmentioning
confidence: 96%
“…The radiotracer of lymphoscintigraphy can enter lymphatic capillaries via the gaps between cell junctions and the intercellular clefts formed by overlapping cells, followed by the lymphatic drainage, and finally gathered in the SLNs to form as a "hot spot" on SPECT image. The SPECT/CT was able to provide functional and anatomical information simultaneously, and locate IM-SLN more accurately (23). Based on these, in our current study, we try to find out the relationship between IM-SLN and consensus guidelines.…”
Section: Discussionmentioning
confidence: 96%
“…13 SPECT/CT can detect SLN that cannot be detected by planar imaging, resulting in upstaging and therapy change in 9.6%-21.3% of patients. 13,14 SPECT/CT can provide accurate anatomical information about SLN and more appropriate therapies for patients (Figure 2). 12 However, its cost is relatively higher.…”
Section: Isotopic Tracer Methodsmentioning
confidence: 99%
“…12,13 It is also useful for scanning invisible, unexplained, or unexpected SLNs (Figure 1). 13 SPECT/CT can detect SLN that cannot be detected by planar imaging, resulting in upstaging and therapy change in 9.6%-21.3% of patients. 13,14 SPECT/CT can provide accurate anatomical information about SLN and more appropriate therapies for patients (Figure 2).…”
Section: Isotopic Tracer Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Borrelli et al [ 9 ] evaluated whether the use of single-photon emission computed tomography/computed tomography (SPECT/CT) improved both visualization and anatomical localization of SN, and whether this additional information would have had any impact on the surgical approach and consequent retrieval of SN in patients with local breast cancer relapse (LBCR). They reported that the addition of SPECT/CT to the standard planar imaging protocol for lymphatic mapping and SN localization in LBCR patients appeared to improve detection of SN and their anatomical localization, and it led to better staging mainly in patients presenting drainage outside the ipsilateral axilla.…”
Section: Oncology—lymphoscintigraphy Updatementioning
confidence: 99%